Photomagnetic therapy and craniosacral therapy for rehabilitation patients with chronic brain ischemia at subacute phase - Fedorov, Serhii (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" Congress. It is dedicated to the photomagnetic therapy and craniosacral therapy for rehabilitation patients with chronic brain ischemia at subacute phase.